A CAMHing Influence: Can a Recruitment Event Inspire Resident Doctors to Train in Child and Adolescent Psychiatry? - Hayley Bowes; Lizzy Donaghy; Parvathy Mohandas; Karen Fulton (BJPsych Open)
Aims: Demand for child and adolescent mental health services (CAMHS) in Northern Ireland (NI) has steadily increased in recent years. Currently, over 50% of families are waiting beyond the recommended nine-week target for assessment. A regional 10-year workforce review outlined the need to expand the CAMHS workforce by 102%, with specific focus on succession planning for psychiatrists. This highlights the need to fill vacant Child and Adolescent Psychiatry (CAP) higher training posts.